2020
DOI: 10.3390/ma13173819
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Wound Healing Potential of Primary Human Oral Fibroblasts and Periodontal Ligament Cells Cultured on Four Different Porcine-Derived Collagen Matrices

Abstract: Xenogenic collagen-based matrices represent an alternative to subepithelial palatal connective tissue autografts in periodontal and peri-implant soft tissue reconstructions. In the present study, we aimed to investigate the migratory, adhesive, proliferative, and wound-healing potential of primary human oral fibroblasts (hOF) and periodontal ligament cells (hPDL) in response to four commercially available collagen matrices. Non-crosslinked collagen matrix (NCM), crosslinked collagen matrix (CCM), dried acellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
0
22
0
1
Order By: Relevance
“…On contrary, both the mesenchymal stromal and pre-osteoblastic cells showed increased proliferative rates on the CCM matrix that were comparable to the cell growth rates on the non-crosslinked HADM and superior compared with the natural NCM and DADM matrices. The impact of the four collagen-based matrices on the migratory, adhesive, and proliferative properties of ST2 and MC3T3-E1 cells, with a better pronounced pro-proliferative effect of HADM and CCM, resembled the impact of the matrices on the functionality of primary human periodontal ligament cells and oral fibroblasts investigated in a recently published study (Lin et al, 2020). This suggests that the difference in the potency of the four matrices to induce changes in the cellular behavior is not cell-specific but rather dependents on their physicochemical characteristics.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…On contrary, both the mesenchymal stromal and pre-osteoblastic cells showed increased proliferative rates on the CCM matrix that were comparable to the cell growth rates on the non-crosslinked HADM and superior compared with the natural NCM and DADM matrices. The impact of the four collagen-based matrices on the migratory, adhesive, and proliferative properties of ST2 and MC3T3-E1 cells, with a better pronounced pro-proliferative effect of HADM and CCM, resembled the impact of the matrices on the functionality of primary human periodontal ligament cells and oral fibroblasts investigated in a recently published study (Lin et al, 2020). This suggests that the difference in the potency of the four matrices to induce changes in the cellular behavior is not cell-specific but rather dependents on their physicochemical characteristics.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the matrices have exhibited sustained growth factor release over 13 days with kinetics that will likely favor the long-term tissue regeneration following surgical reconstructive periodontal therapies. We have further demonstrated that the investigated collagen-based matrices successfully promote migration, adhesion, and proliferation of cell types involved in oral soft tissue regeneration, namely primary human oral fibroblasts and periodontal ligament cells ( Lin et al, 2020 ). The current study extends the in vitro investigations on the four 3D matrices in relation to their ability to trigger osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 83%
“…Primary hPDLCs and hOFs were obtained from three donors each using the tissue explant technique as described previously [ 9 ]. The collection of donor tissue from systemically and periodontally healthy individuals below 35 years had received an approval by the Ethics Committee, Berne, Switzerland (ethical code ID 2018-00661 from 13.08.2018).…”
Section: Methodsmentioning
confidence: 99%
“…RNA, quantified spectrophotometrically and reverse transcribed by using the Transcriptor First Strand cDNA Synthesis Kit (Roche, Basel, Switzerland), was subjected to qPCR using the FastStart Universal SYBR Green Master ROX (Roche) and the primer sequences listed in Table 1 . The PCR was carried out in a QuantStudio 3 instrument (Applied Biosystems, Rotkreuz, Switzerland) as described [ 9 ]. The efficiency ∆∆Ct method was used to calculate gene expression levels normalized to GAPDH and calibrated to controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation